2017
DOI: 10.3390/aerospace4020021
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Aerodynamics, Including Dynamic Stall, for Comprehensive Analysis of Helicopter Rotors

Abstract: Abstract:To fulfill the objective of a predictive tool for rotorcraft, comprehensive analysis (CA) needs to be capable of providing both accurate and time-efficient predictions of rotor air loads and structural loads. The more recent methodology based on comprehensive analysis coupled with high-fidelity computational fluid dynamics (CFD) has shown improved predictions of air loads, but it has not the strength of computational efficiency and the versatility of stand-alone CA. The present article is concerned wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…where ν t is defined as ν t = µ t ρ =ν f v1 . The working variableν is obtained from the SA transport Equation (6). In addition, the following model coefficients are used:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ν t is defined as ν t = µ t ρ =ν f v1 . The working variableν is obtained from the SA transport Equation (6). In addition, the following model coefficients are used:…”
Section: Methodsmentioning
confidence: 99%
“…Stall phenomena, typically dynamic stall, impact on designing and analyzing lift surfaces. For example, conventional helicopter main rotor blades frequently encounter dynamic stall in high-speed forward flight conditions [2][3][4][5][6][7]. The blade stall can occur in the retreating side because the blade needs to pitch up in order to balance aerodynamic forces.…”
Section: Introductionmentioning
confidence: 99%
“…The equations are iterated in pseudo-time due to the non-physical time derivative of pressure. In order to advance the system of Equations (1) and (2) in real time, a dual-time stepping procedure needs to be employed for which a real time derivative is added to the momentum equation. The time-step has to satisfy the following condition as…”
Section: The Artificial Compressibility Methodsmentioning
confidence: 99%
“…Despite the advances made in the field of computational fluid dynamics over the past decades, predicting flow patterns around aerodynamic shapes remains a challenge for aerospace applications. The flow around a wing can have a transonic behaviour which, at high angles of attack, may be supplemented by flow separation, strong crossflow gradients as well as a hysteresis in the lift slope [1,2]. Traub [3] highlighted further that at low Reynolds number flows, laminar separation bubbles exist which have an inherently unsteady behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…However, a clear single best model was not found. Gonzalez and Munduate (2007) and Wala et al (2018) both showed promising results using modified and optimized Beddoes-Leishman models compared with experimental data. Inaccuracies in dynamic stall models may be due to the abovedescribed fact that they are not properly designed for high angles of attack and that there are some of them that do not specifically describe vortex shedding behaviour.…”
Section: Introductionmentioning
confidence: 93%